2017
DOI: 10.4314/ijs.v19i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoecological studies of quaternary sediments from the University of Lagos, Nigeria

Abstract: The knowledge of changes in past ecological conditions during the Quaternary period of Nigeria is still incipient. This necessitated a palaeoecological investigation through drilled sediments of a 45 m borehole in a swampy area at the University of Lagos, in order to ascertain possible changes in the past ecological conditions of the study area over time. Sixteen sediment samples were collected at intervals of 3 m between the depth of 0.00 m and 45.00 m and subjected to palynological, lithological, pH and sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These studies identified several plant species dominant on the Nigerian coast. Apart from the mangrove occupied by specific species, for example, Rhizophora spp., Acrostichum aureum Cav., and anthropogenic impacts on coastal communities of Lagos state Adekanmbi & Alebiosu, 2017;Adeniyi et al, 2016;Ajikah et al, 2019;Orijemie & Sowunmi, 2014;Oyebanji et al, 2020;Sowunmi, 2004). The above studies failed to provide a detailed floristic inventory of the coastal areas of Lagos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies identified several plant species dominant on the Nigerian coast. Apart from the mangrove occupied by specific species, for example, Rhizophora spp., Acrostichum aureum Cav., and anthropogenic impacts on coastal communities of Lagos state Adekanmbi & Alebiosu, 2017;Adeniyi et al, 2016;Ajikah et al, 2019;Orijemie & Sowunmi, 2014;Oyebanji et al, 2020;Sowunmi, 2004). The above studies failed to provide a detailed floristic inventory of the coastal areas of Lagos.…”
Section: Introductionmentioning
confidence: 99%
“…and Nypa fruticans Wurmb, other species (e.g., Andropogon spp, Chromolaena odorata (L.) R.M.King & H.Rob., Cyperus javanicus Houtt., and Typha domingensis Pers are found in equivalent wetland habitats. A handful of past studies have also revealed the extent of vegetation change and anthropogenic impacts on coastal communities of Lagos state (Adekanmbi et al, 2017; Adekanmbi & Alebiosu, 2017; Adeniyi et al, 2016; Ajikah et al, 2019; Orijemie & Sowunmi, 2014; Oyebanji et al, 2020; Sowunmi, 2004). The above studies failed to provide a detailed floristic inventory of the coastal areas of Lagos.…”
Section: Introductionmentioning
confidence: 99%